2016
DOI: 10.1111/imj.13116
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Australasian geriatricians’ satisfaction with, and preferences for, continuing professional development

Abstract: Respondents perceived the face-to-face CPD opportunities currently available to them as valuable for their CPD but seek additional, flexible products to enable CPD participation based on individual needs and preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…For example, recent study by Maher et al 6 found all three factors to be significant barriers to hospital doctors in Ireland. This pattern has been reflected in the international literature; in a survey of Australasian geriatricians; Etherton-Beer et al 7 also found time constraints (both regarding professional and non-professional commitments) to be a major barrier, however, this study did not find cost to be a major barrier, potentially reflecting differences in remuneration for doctors across countries. Similar results were found by Weiland et al 8 and a second study by Dent et al, 9 which also expanded on these results with qualitative items which indicated that fatigue, staff shortages, valuing family time and a lack of relevant, good quality CPD activities for doctors were also prominent barriers.…”
Section: Previously Identified Barriers and Facilitators To Participationsupporting
confidence: 61%
See 1 more Smart Citation
“…For example, recent study by Maher et al 6 found all three factors to be significant barriers to hospital doctors in Ireland. This pattern has been reflected in the international literature; in a survey of Australasian geriatricians; Etherton-Beer et al 7 also found time constraints (both regarding professional and non-professional commitments) to be a major barrier, however, this study did not find cost to be a major barrier, potentially reflecting differences in remuneration for doctors across countries. Similar results were found by Weiland et al 8 and a second study by Dent et al, 9 which also expanded on these results with qualitative items which indicated that fatigue, staff shortages, valuing family time and a lack of relevant, good quality CPD activities for doctors were also prominent barriers.…”
Section: Previously Identified Barriers and Facilitators To Participationsupporting
confidence: 61%
“…These barriers-time and cost-are the barriers most likely to be mentioned in previous research, especially in working environments experiencing staff shortages. [6][7][8] The desire for more online-based CPD as a result of time restrictions is interesting, given the perceptions that CPD activities are of limited benefit outlined in theme 3. Previous research has shown online CPD to be the least effective in changing doctor behaviour or patient outcomes when compared with more interactive in-person activities, suggesting that doctors may favour CPD activities which have fewer tangible benefits to their practice.…”
Section: Theme 4: Workplace Challengesmentioning
confidence: 99%
“…Moreover, other studies suggest that, even in an era of increasing uptake of e-learning [ 27 ], in-person learning activities with peers and experts remain popular among practicing clinicians and, at times, may be favored over technology-based learning [ 28 31 ]. This underscores the importance of providing multifaceted, or blended, options for the diversity of learning needs and preferences [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…While these preferences include point of care knowledge acquisition and internet learning, a substantial percentage of physicians still prefer traditional methods of educational delivery such as Grand Rounds or regularly scheduled series (RSS). 4,5 RSS enable physicians to maintain competence and incorporate new knowledge to improve quality care for patients and communities. As defined by the Accreditation Council for Continuing Medical Education, 6 RSS are series with multiple sessions that occur on an ongoing basis (offered weekly, monthly, or quarterly) and are primarily planned by and presented to the accredited organization's professional staff.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, some groups have begun to relook at the educational preferences and barriers to education for physicians, using national surveys, to help shape the future of CME. 4,5 While surveys are useful tools, they are limited to the questions that are asked and may not be the best methods to determine the xx mechanism of action of CME. Given that the desired and resultant changes from RSS may not always align, the open-ended nature of qualitative analysis may complement these approaches and be better positioned to help identify the features of CME that are the most likely to result in both expected and unexpected changes from a learner's perspective.…”
Section: Introductionmentioning
confidence: 99%